PHYSICAL CULTURE AND SPORT IN THE LIFE OF MODERN SOCIETY - B.Usmanov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the role of physical culture and sports in the life of modern society. The positive role of physical activity on the functional state of the human body is noted. Sport as a prevention of deviant behavior in modern society.